2001
DOI: 10.1161/01.cir.103.17.2171
|View full text |Cite
|
Sign up to set email alerts
|

Echolucent Plaques Are Associated With High Risk of Ischemic Cerebrovascular Events in Carotid Stenosis

Abstract: Background-The purpose of the study was to assess in a prospective design whether plaque morphology is associated with risk of ischemic stroke and other cerebrovascular events in subjects with carotid stenosis. Methods and Results-A total of 223 subjects with carotid stenosis (123 with 35% to 49% degree of stenosis, 100 with 50% to 99% stenosis) and 215 control subjects matched by age and sex who participated in a population health survey at baseline were followed up for 3 years. Plaque echogenicity was assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
412
1
15

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 538 publications
(449 citation statements)
references
References 30 publications
21
412
1
15
Order By: Relevance
“…Large‐artery atherosclerosis is classified according to rather rigid TOAST criteria, which requires occlusion or ≥50% stenosis in a related artery 7, not paying attention to atherosclerotic plaque instability which may lead to arterio‐arterial embolism even from stenosis of low or moderate degree 33, 34. Hence, true large‐artery atherosclerosis is in general likely to be underestimated due to an arbitrary TOAST definition.…”
Section: Discussionmentioning
confidence: 99%
“…Large‐artery atherosclerosis is classified according to rather rigid TOAST criteria, which requires occlusion or ≥50% stenosis in a related artery 7, not paying attention to atherosclerotic plaque instability which may lead to arterio‐arterial embolism even from stenosis of low or moderate degree 33, 34. Hence, true large‐artery atherosclerosis is in general likely to be underestimated due to an arbitrary TOAST definition.…”
Section: Discussionmentioning
confidence: 99%
“…Several lines of evidence suggest that this could possibly reflect a stabilizing effect on the lesion. Previous studies have shown that echogenic plaques have a more stable phenotype and are associated with a lower risk for development of clinical events [6,7].…”
Section: Discussionmentioning
confidence: 99%
“…The possibility to assess carotid plaque morphology in terms of echogenicity expressed as gray scale median (GSM) on ultrasound images has been explored during recent years. The results of these studies indicate that echolucent plaques are associated with an increased risk for ischemic cerebrovascular events independent of degree of stenosis [6,7]. Echolucent plaques have been shown to contain more lipids [8], macrophages [9], and elastin [10] in comparison to more echogenic lesions.…”
Section: Introductionmentioning
confidence: 93%
“…This evidence has been buoyed by the Tromsø study which followed up 223 patients with 35-99% stenosis and 215 controls for 3 years. It found that the RRs of ipsilateral cerebrovascular events for the predominantly echolucent and wholly echolucent groups were 3.5 (95% CI, 1.0 -12.4) and 3.6 (95% CI, 0.8 -16.8) respectively compared to the echogenic plaques (Mathiesen, Bonaa, & Joakimsen 2001). A further study (Grønholdt et al 2001) looked at the RR of ischaemic stroke, as opposed to cerebrovascular events, between the two groups and found it to be 3.1 (95% CI, 1.3 -7.3).…”
Section: Ultrasound Techniquesmentioning
confidence: 99%